Ibn al-Nafis contribution in urology progress practices - Mohd Dom, Azratul Ashimah Nur; Kabbashi, Nassereldeen Ahmed (IIUM Press, 2011)
The objective of this chapter is to explain about the progression of urology that had been made by Ibn al-Nafis, one of the well-known Muslim physicians. Urology is another branch of medicine that based on the treatment of disorders and diseases related to male and female genito-urinary organs including the kidney, ureters, bladder, prostate and genitalia. The significance of this study to highlight about urology study progress done by Ibn al-Nafis, where he made the progress based on Ibn Sina and Greek Galen's work. The methods of findings were based on a collection of literature such as writing like journals, list or report and books as well